Owner-reported treatments and outcomes of perceived injuries to the thoracic and pelvic limb of agility dogs - Alva, Bianca M.; Pechette Markley, Arielle; Shoben, Abigail; Kieves, Nina R. (Frontiers in Veterinary Science, 2024)
The aim of this study was to identify the type of veterinary care sought by handlers of injured agility dogs, the types of treatments the dogs received, and the timeframe for return to training and competition. Procedures: Owners of agility dogs completed an internet-based survey. They were instructed to report injuries that had kept the dog from training or competing for over a week, identify which area(s) of the body had been injured and answer questions about the most severe injury to each body part. Additional questions included if handlers had sought veterinary care, who primarily determined treatment, type of treatment(s), and length of time before the dog could return to full training and competition.Results: This sample included data on 1,714 total injuries from 1,256 unique dogs. Handlers sought veterinary care for over 80% of injuries across all anatomical locations. Handlers were most likely to seek specialty veterinary care for reported injuries to the stifle (71%), iliopsoas (63%) and tibia (61%), and least likely for reported injuries to the carpus (34%), metatarsus (33%) and metacarpus (22%). Treatment of reported injuries to the antebrachium and stifle were most likely to be directed by a veterinarian (>70%), while reported injuries of the thigh (51%) and hip (53%) were least likely. Rest was the most common treatment for all injuries. Return to sport within 3 months was common (>67%) for most perceived injury locations, though dogs with reported stifle injuries took longer to return to competition and had a higher rate of retirement. Conclusion and Clinical Relevance: Owners of agility dogs have a high rate of seeking veterinary care for injuries. Overall return to sport rates were high, with the stifle being the notable exception. Future studies regarding specific treatment of injuries in agility dogs, and how injuries and their treatment affect return to agility after injury are required to provide optimal care protocols for these canine athletes.